Analysis of the degree of ruralization at the territorial level - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
This paper presents the main characteristics of the workforce in rural areas. The primary objective of the study is to highlight the importance of the workforce resource in the Romanian rural space, as a key element of sustainable development, given that 47.7% of the population resides in rural areas. The study aims to analyze the implication of the degree of ruralization at the territorial level for the 41 counties, on the workforce and the level of economic development. According to the conducted statistical-economic analysis at the national level, it is observed that in regions where the process of ruralization is pronounced, economic outcomes are less impressive, and this trend can largely be attributed to the lower average productivity level of the workers. Stimulating the development of rural areas in Romania is considered necessary, as is enhancing the quality of the workforce in the rural environment.
Keywords: Q01; O12; O15; 330; ruralization; rural development; workforce; agriculture; correlation